Siamese Twin Troubles: Structural and Regulatory Transformations in Unequal Thailand. (27th July 2022) - Kanchoochat, Veerayooth
Abstract : This paper takes an institutional approach to inequality in Thailand by exploring the country's structural and regulatory transformations. It discusses how Thailand's transition from agriculture to industry and services has been impeded by both the demand and supply sides of government subsidies since the 1950s. The relative failure of structural transformation has slowed down economic catch‐up and widened the well‐being gap between those inside and outside the agricultural sector. Furthermore, while regulatory transformation has mitigated state‐led malaise in certain Asian economies, post‐1997 reform in Thailand has incentivized unconventional political actors, such as academics, medical doctors and civil society leaders, to make collective efforts in toppling elected governments in exchange for gaining selection into oversight agencies. The case of Thailand indicates how regulatory reform may create perverse incentives that adversely affect democratization, decentralization, competition, and taxation. Dealing with inequality therefore requires a big push toward progressive structural and regulatory transformations altogether.